Strengthening And Retrofitting Reinforced Concrete Column Using Concrete Jacketing Method As External Confinerment: An Overview - I’zaz Imtiyaz Shofa’; Parmo; Kusnul Prianto (Jurnal Serambi Engineering, 2026)
Reinforced concrete (RC) jacketing is a universally recognized effective technique for strengthening and repairing structurally compromised columns. This paper integrates previous research to evaluate the effectiveness of RC jacketing in improving the axial and seismic performance of columns through external confinement. The literature review demonstrates that RC jacketing significantly improves the load-bearing capacity, ductility, and stiffness of columns. Key factors influencing performance are identified: surface preparation, use of mechanical connectors, adhesives, and the number of coated sides, with four-sided jacketing being particularly effective. The literature review also explores practical applications, such as partial jacketing at column corners and preload member jacketing, along with identifying their cost-effectiveness in economic terms compared to full renovation. Furthermore, innovative approaches such as the use of sustainable bamboo reinforcement and hybrid techniques combining jacketing with additional beams have the potential to improve efficiency and environmental sustainability. It can be demonstrated that RC jacketing has proven to be a reliable, economically and structurally viable solution for rehabilitation.